Conservative treatment versus surgical excision of ovarian dermoid cysts: Impact on ovarian stimulation and IVF cycle success. Issue 3 (30th December 2019) - Hernandez‐Nieto, Carlos; Lee, Joseph A.; Gonzalez, Katherine; Mukherjee, Tanmoy; Copperman, Alan B.; Sandler, Benjamin
Abstract: Objective: To analyze outcomes of IVF treatment among women diagnosed with an ovarian dermoid cyst (DC). Methods: Retrospective analysis of women with an ovarian DC who underwent IVF with fresh blastocyst transfer at a single center in New York from January 2010 to March 2018. Outcomes were compared between women with conservative treatment and those with surgical excision of the DC. Multivariate logistic regression was used to assess associations between variables and the presence of a DC during treatment. Results: Overall, 119 women with a DC were included. No differences were found in demographic characteristics, controlled ovarian hyperstimulation parameters, and IVF outcomes between women with an intact DC (n=65, 54.6%) and those who underwent cystectomy (n=54, 45.4%) (all P <0.05). Similarly, there was no difference in anti‐Mϋllerian hormone and basal antral follicle count among women with a DC (respectively, β=−0.1, P =0.8, and β=−1.0, P =0.28) or resected DC (respectively, β=0.9, P =0.07, and β=1.5, P =0.08) as compared with control women with no DC (n=352). Conclusion: Ovarian reserve, embryo implantation and IVF success rates were not lower in the presence of an ovarian DC. Surgical therapy, if indicated, can be safely postponed until family planning goals have been achieved. Abstract : During assisted‐reproduction treatment, ovarian reserve markers, embryo implantation, and IVF success rates did not decrease with the presence or removal of an ovarian dermoid cyst.